2015
DOI: 10.1111/deci.12141
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Impact of FSC Certification in the United States: A Contingency Perspective

Abstract: This article focuses on an important and emergent standard for sustainable operations management: the Forest Stewardship Council (FSC) certification. Unlike similar certifications, its focus is on the entire upstream supply chain, reflecting the criticality of supply chain management to ensure sustainable products. We investigate the financial impact from FSC certification, offering valuable decision support for managers considering this certification. Taking a contingency perspective, we view a firm's supply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 87 publications
(126 reference statements)
2
28
0
Order By: Relevance
“…Results of this study suggest that FSC certifi cation is a precondition for competitiveness for Croatian wood industry companies. These fi ndings are consistent with the fi ndings of Narasimhan et al (2015), who confi rmed that upstream fi rms (companies at the beginning of supply chain), to which Croatian wood processing companies mostly belong, face coercive pressure from their business customers, and thus might choose to certify even if the benefi ts of certifi cation are not apparent. Although fi nancial benefi ts have not been proven significantly, the share of certifi ed products in total revenue is quite signifi cant.…”
Section: Rasprava I Zaključaksupporting
confidence: 86%
See 2 more Smart Citations
“…Results of this study suggest that FSC certifi cation is a precondition for competitiveness for Croatian wood industry companies. These fi ndings are consistent with the fi ndings of Narasimhan et al (2015), who confi rmed that upstream fi rms (companies at the beginning of supply chain), to which Croatian wood processing companies mostly belong, face coercive pressure from their business customers, and thus might choose to certify even if the benefi ts of certifi cation are not apparent. Although fi nancial benefi ts have not been proven significantly, the share of certifi ed products in total revenue is quite signifi cant.…”
Section: Rasprava I Zaključaksupporting
confidence: 86%
“…Numerous studies have attempted to determine whether the certifi cation brings any benefi t and why certifi cate holders decided to implement chain of custody standards (Rickenbach and Overdevest, 2006;Vlosky et al, 2009;Bowers et al, 2012;Narasimhan et al, 2015 (Bowers et al, 2012). Price premium and market-based benefi ts from certifi cation were among the lowest ranked reasons (Rickenbach and Overdevest, 2006;Bowers et al, 2012).…”
Section: Literature Review 2 Pregled Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Green et al [6] showed that the implementation of green purchasing leads directly to improved economic performance of manufacturing firms, and Yang [7] found the reduced environmental impacts of a firm improve its competitiveness, in terms of service quality, productivity, and profits. More recently, Narasimhan et al [24] extended this view by exploring the role of the involved entities' supply chain positions. They found that companies closer to final consumers achieve greater financial benefits from Forest Stewardship Council certification, a widely-acknowledged international standard in the management and supply of sustainably produced timber.…”
Section: Environmental Sustainability and Firm Performance: Mixed Finmentioning
confidence: 99%
“…A common method for academic researchers and industry practitioners to control for industry effect is to rely on the industry classification to cluster firms with similar firm characteristics, such as business operations and products/services, into groups. The industry classification system therefore is important for information users in business as it provides a systematic way of identifying a group of similar companies (Kahle & Walkling, 1996;King & Slotegraaf, 2011;Narasimhan, Schoenherr, Jacobs, & Kim, 2015) and understanding the structure of economy (Christensen, 2013). It is well established that better industry classification contributes to better analysis results, compared with only considering firm size in the comparison (Kahle & Walkling, 1996).…”
Section: Introductionmentioning
confidence: 99%